Paper Folding Art Activities in Early Childhood Learning - Satrial, Ardi; Adriyani, Sylva; Rahmi, Azvi; Indria, Anita; Utami, Rahmi Dwi (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2024)
The problem in writing this thesis is the delay in the development of fine motor skills in children aged 5-6 years. Based on this, the author is interested in further research, namely